An Approach for Estimating the Design Flood Flowline on Developed Rivers - ŞENTÜRK, H. ALİ (TÜBİTAK, 2002)
The stages produced by the major floods on developed rivers (like the Rhine in Europe, the Mississippi and the Red rivers in the USA) indicate that existing stage-discharge relationships are usually several feet higher than the stage-discharge relationship if the rivers were natural or partially developed. The objectives of this paper are to discuss the problem of estimating the flowline for the design flood on developed rivers, and in so far as is possible with existing data, point to a rational methodology for developing this estimate. The problem is approached in two stages. First, the stage-discharge relations in undeveloped and developed rivers are analysed and contrasted qualitatively to provide an indication of expected trends. Second, stage-discharge records on a developed river and an estimate of the energy gradient are combined with a computer solution of several methods for computing channel roughness to provide a plot of roughness (Manning's n) versus discharge. Extrapolation of this plot to the design discharge yields a range of roughness values that can be used to estimate flowlines associated with the design discharge.
Keywords: River Hydraulics, Developed Rivers, Flood-stage Relation, Maximum Flood, Design Discharge